Money, financial instability and stabilization policy - Wray, L. Randall; Forstater, Mathew (Cheltenham : Edward Elgar, 2006)
Money, Financial Instability and Stabilization Policy consists of original articles by leading post Keynesians, Kaleckians and other heterodox economists from the developed and developing world.
Includes bibliographical references and index.
oif 01/08/16, ijb 07/03/2019
Loan
Keywords: Money; Monetary policy; Keynesian economics; Economic stabilization